2018
DOI: 10.13005/bpj/1604
|View full text |Cite
|
Sign up to set email alerts
|

Compared to Conventional Dressing Techniques, Tranexamic Acid Injection Provide Better Surgical Outcomes in Spinal Fusion Surgery

Abstract: The use of mechanical and chemical hemostatic control techniques in spinal fusion surgery is common in Indonesia. However, there has been no study comparing the two in a single clinical trials. This study aims to find out which best of tranexamic acid injection, a bulky compression dressing and a standard dressing in providing surgical outcomes in spinal fusion surgery. Thirty patients were grouped into three, 10 patients each. To Group 1, tranexamic acid at a dose of 500 mg/ml was administered pre operation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…Intraoperative blood loss and postoperative drainage volume are of great significance to assess the blood protection effect during the operation. In the current research, it was unveiled that the intraoperative blood loss and postoperative drainage volume in the control group were markedly higher than those in all experimental groups (p < 0.05), which was consistent with Fauzi et al results [23]. It indicated that TXA could effectively reduce the bleeding and blood transfusion in patients during scoliosis correction surgery.…”
Section: Peripheral Blood Mononuclear Cells (Pbmcs) Expression In the S2 Group And D0 Groupsupporting
confidence: 90%
“…Intraoperative blood loss and postoperative drainage volume are of great significance to assess the blood protection effect during the operation. In the current research, it was unveiled that the intraoperative blood loss and postoperative drainage volume in the control group were markedly higher than those in all experimental groups (p < 0.05), which was consistent with Fauzi et al results [23]. It indicated that TXA could effectively reduce the bleeding and blood transfusion in patients during scoliosis correction surgery.…”
Section: Peripheral Blood Mononuclear Cells (Pbmcs) Expression In the S2 Group And D0 Groupsupporting
confidence: 90%